Chitosan/gelatin porous scaffolds assembled with conductive poly(3, 4-ethylenedioxythiophene) nanoparticles for neural tissue engineering. Issue 24 (30th May 2017) - Wang, Shuping; Sun, Changkai; Guan, Shui; Li, Wenfang; Xu, Jianqiang; Ge, Dan; Zhuang, Meiling; Liu, Tianqing; Ma, Xuehu
Abstract : An electrically conductive scaffold was prepared by assembling PEDOT on a chitosan/gelatin porous scaffold via in situ interfacial polymerization. Abstract : Electroactive biomaterials are widely explored as scaffolds for nerve tissue regeneration. Poly(3, 4-ethylenedioxythiophene) (PEDOT) is a conductive polymer that has been chosen to construct tissue engineered scaffolds because of its excellent conductivity and non-cytotoxicity. In the present study, an electrically conductive scaffold was prepared by assembling PEDOT on a chitosan/gelatin (Cs/Gel) porous scaffold surface via in situ interfacial polymerization. The hydrophilic Cs/Gel hydrogel was used as a template, and PEDOT nanoparticles were uniformly assembled on the scaffold surface. The static polymerization of the 3, 4-ethylenedioxythiophene (EDOT) monomer at the interface between the aqueous phase and the organic phase was accompanied by the formation of the PEDOT-assembled Cs/Gel scaffolds. PEDOT/Cs/Gel scaffolds were characterized by scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), and Raman spectroscopy. The results confirmed the deposition of PEDOT nanoparticles with the mean diameter of 50 nm on the Cs/Gel scaffold channel surface. Compared to the Cs/Gel scaffold, the incorporation of PEDOT on the scaffold increased the electrical conductivity, hydrophilicity, mechanical properties and thermal stability, whereas decreased the water absorption and biodegradation. For biocompatibility, PEDOT/Cs/Gel scaffolds, especially the 2PEDOT/Cs/Gel scaffold group, significantly promoted neuron-like rat pheochromocytoma (PC12) cell adhesion and proliferation. The results of both the gene expression and protein level assessments suggested that the PEDOT-assembled Cs/Gel scaffold enhanced the PC12 cellular neurite growth with higher protein and gene expression levels. This is the first report on the construction of a conductive PEDOT/Cs/Gel porous scaffold via an in situ interfacial polymerization method, and the results demonstrate that it may be a promising conductive scaffold for neural tissue engineering.